2020
DOI: 10.1177/0300891620950472
|View full text |Cite
|
Sign up to set email alerts
|

Emerging functions of PRKDC in the initiation and progression of cancer

Abstract: The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is encoded by the protein kinase, DNA-activated, catalytic polypeptide ( PRKDC) gene. DNA-PKcs plays a major role in nonhomologous end joining DNA repair, and it has been identified to be an important factor in tumor progression and metastasis. DNA-PKcs may have opposite effects in diseases, depending on the cell and tissue types. In this review, we discuss its role in various tumors. High levels of DNA-PKcs are directly associated with prognosis, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Further analyses showed that SPP1 significantly contributed to tumor differentiation. SPP1 was discovered to be upregulated in undifferentiated tumors in Protein Kinase, DNA-Activated, Catalytic Polypeptide (PRKDC) [ 18 20 ]. It was encouraging that SPP1 is related to clinical-pathologic variables at the mRNA level, and PRKDC with increased SPP1 expression could progress to an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses showed that SPP1 significantly contributed to tumor differentiation. SPP1 was discovered to be upregulated in undifferentiated tumors in Protein Kinase, DNA-Activated, Catalytic Polypeptide (PRKDC) [ 18 20 ]. It was encouraging that SPP1 is related to clinical-pathologic variables at the mRNA level, and PRKDC with increased SPP1 expression could progress to an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it suggests that the inhibition of TTK by MS13 treatment may inhibit cell proliferation and induce apoptosis in AIPC cells. PRKDC is a critical component of DNA repair machinery, and its expression is implicated in tumour progression, metastasis and migration (Yin et al, 2020). The PRKDC knockdown has been reported to attenuate cell proliferation and metastasis in PCa cells (Goodwin et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the two RBPs with the highest mutation frequency, PRKDC and HELZ2, were searched on the cBioportal platform. The PRKDC gene encodes the catalytic subunit of DNA-dependent protein kinase (DNA-PK) [ 29 ]. Together with Ku70/Ku80 heterodimeric protein, PRKDC has an effect on DNA double-strand break repair and recombination [ 30 ].…”
Section: Discussionmentioning
confidence: 99%